Removal of the emerging contaminants carbamazepine, diclofenac, and amoxicillin from wastewater by simultaneous application of ultrasound, adsorption, and membrane filtration - Secondes, Mona Freda N. (College of Engineering, University of the Philippines Diliman, 2014)
The presence of emerging contaminants (ECs) at low levels in the environment is linked to serious problems of biodiversity loss, emergence of highly resistant microbial strains, human infertility and cancer. Conventional treatment methods are not capable of removing ECs, thus advanced treatment of wastewater is necessary before disposal or reuse. This paper investigated the efficiency of a novel hybrid USAMe process that applied membrane ultrafiltration, activated carbon adsorption and ultrasound irradiation simultaneously to remove ECs. Diclofenac, carbamazepine and amoxicillin were chosen for this study because of their high occurrences and significant environmental risks. Removal mechanisms and enhancement effects were analyzed through the investigation of single-method and dual-method processes apart from the USAMe process. Influence of certain factors such as adsorbent dose, ultrasonic frequency and presence of natural organic matter to membrane performance were studied. Performance was measured in terms of EC removal and fouling control through TMP monitoring. Abatement of fouling was greatly enhanced and almost complete EC removals were achieved in the USAMe process within the duration of the experiments. The enhancement was attributed to the combined effect of activated carbon adsorption and ultrasonic cavitation, the former providing superior contribution. This study demonstrates that the novel USAMe process is a viable option for advanced wastewater treatment.